PENGEMBANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SISWA MAGANG MELALUI METODE PROFILE MATCHING: Profile mathing, SPK, competence, Internship - -, Mulyadi; -, Nurdiana (JURNAL AKADEMIKA, 2019)
The purpose of this research is to build a decision support system that can help field coordinators and the Department of Manpower and Transmigration of Jambi Province to determine the apprentices to be sent to Japan in this study using the profile mathing method, one of the methods in the profile mathing decision making system is a process that is very important in HR management where competence (ability) is first determined. Decision Support System for Selection of Japanese Internship Participants Using the Web-Based Profile Matching Method can facilitate the performance of the Jambi Province Manpower and Transmigration Office. can assist in the selection of apprentice participants to Japan.